Physical and chemical composition of the must and white wine of grapevine cultivars in response to rootstocks - Rodrigues da Silva, Marlon Jocimar [UNESP]; Tecchio, Marco Antonio [UNESP]; Moura, Mara Fernandes; Brunelli, Luciana Trevisan [UNESP]; Imaizumi, Vitor Massami [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Empresa Brasil Pesq Agropec, 2015)
The objective of this work was to evaluate the influence of the rootstocks 'IAC 766 Campinas' and '106-8 Mgt Riparia do Traviu' on the physicochemical characteristics of must and wine of the 'IAC 116-31 Rainha', 'IAC 21-14 Madalena', and 'BRS Lorena' grapevines. Grape must was evaluated for pH, soluble solids (SS), total acidity (TA), and SS/TA ratio. In wine, the following physicochemical analyses were performed: density, alcohol content; total, volatile, and fixed acidity; pH; dry extract; reducing sugars; reduced dry extract; alcohol in weight/reduced dry extract; free and total sulfur dioxide; total polyphenol index (I 280); total polyphenols; flavonoids; and antioxidant activity. Must characteristics of 'IAC 21-14 Madalena' were not affected by rootstocks; however, the 'IAC 766 Campinas' rootstock promoted higher SS/TA in 'IAC 116-31 Rainha' must and lower SS/TA in 'BRS Lorena' must. The 'IAC 766 Campinas' and '106-8 Mgt Riparia do Traviu' rootstocks influenced pH and alcohol content of 'IAC 116-31 Rainha' wine, the dry extract of 'IAC 21-14 Madalena' wine, and the fixed acidity of 'BRS Lorena' wine. There was no influence of the rootstocks on the phenolic compounds and antioxidant activity of wines.
Keywords: Vitis vinifera; Vitis labrusca; classical analyses; polyphenols; table wine